(untitled) (Texas Journal of Medical Science, 2022)
This study was conducted on 370 patients from health centers and private clinics from February 2021 to December 2021.The samples were examined by the direct swab method. The DMFT was used in accordance with the recommendations of the World Health Organization. The current study showed a decline in the level of oral care among smokers, as well as the results showed that the total infection rate of the parasite T.tenax was the highest infection in smokers, reaching 95.6%،and the lowest infection was among non-smokers, reaching 20.15%.The highest incidence was in the age groups more than 50 years. In this study, SPSS statistical analysis was used, and no significant differences were recorded